2014
DOI: 10.1016/j.vetmic.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Use of a proposed antimicrobial susceptibility testing method for Haemophilus parasuis

Abstract: The aim of this study was to examine the antimicrobial susceptibility of 97 Haemophilus parasuis cultured from Australian pigs. As there is no existing standard antimicrobial susceptibility technique available for H. parasuis, methods utilising the supplemented media, BA/SN for disc diffusion and test medium broth (TMB) for a microdilution technique, were initially evaluated with the reference strains recommended by the Clinical and Laboratory Standards Institute. The results of the media evaluation suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 14 publications
1
29
1
Order By: Relevance
“…High level of resistance to tetracycline is in agreement with findings in previous studies and our previously published results (Wissing et al 2001;Pejsak et al 2005;Dayao et al 2014). In contrast, low level of resistance to tetracycline has been reported from China (3.6%) but a different breakpoint ≤ 8 μg/ml was used in the study (Zhou et al 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…High level of resistance to tetracycline is in agreement with findings in previous studies and our previously published results (Wissing et al 2001;Pejsak et al 2005;Dayao et al 2014). In contrast, low level of resistance to tetracycline has been reported from China (3.6%) but a different breakpoint ≤ 8 μg/ml was used in the study (Zhou et al 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Based on this proposed criteria, 12 (40%) isolates from our study would belong to a resistance pattern. Tulathromycin resistance has recently been identified in H. parasuis isolates from Australia (Dayao et al 2014). An experimental challenge study demonstrated a failure in protection and development of polyserositis with a high isolation rate of H. parasuis with the metaphylactic use of tulathromycin (Palzer at al.…”
Section: Discussionmentioning
confidence: 99%
“…H. parasuis is a fastidious organism which requires specific ingredients or supplements to achieve visible growth in broth, and hence, media which are used to test rapidly growing bacteria are not adequate (6,7). As a consequence, no validated and standardized method is available (7,8), and many diagnostic laboratories are currently unable to offer susceptibility testing of this very important pathogen in pig production.…”
mentioning
confidence: 99%
“…H. parasuis is a fastidious organism which requires specific ingredients or supplements to achieve visible growth in broth, and hence, media which are used to test rapidly growing bacteria are not adequate (6,7). As a consequence, no validated and standardized method is available (7,8), and many diagnostic laboratories are currently unable to offer susceptibility testing of this very important pathogen in pig production. However, a few studies investigated the susceptibility status of H. parasuis isolates quantitatively by using media such as veterinary fastidious medium (VFM) or Haemophilus test medium (HTM) for broth microdilution susceptibility testing (7,(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
See 1 more Smart Citation